Why is Europe lagging behind? - Ilmo Pyyhtiä (Bank of Finland, 2007)
This paper builds on the literature on growth in searching for explanations for the divergent growth performance between the EU countries and the United States.We emphasise the role of R&D investment and perhaps different degrees of elasticity of substitution between capital and labour.We estimate two different production functions, namely Cobb-Douglas and CES specifications, with physical capital, a measure of labour, and residual 'technical trend' as inputs.Our first finding is that in many ICT-producing and using countries such as Denmark, Finland, Ireland, Sweden and the United States technical progress has been accelerating during the past decade.Secondly, this speeding up of technical progress has been associated with R&D investment and perhaps with increasing elasticity of substitution between capital and labour.Hence, our results suggest that there is no growth paradox in Europe: the R&D factor and the elasticity of substitution between capital and labour which have been known to be important factors of economies' growth potential, actually explain a significant part of the divergent growth performance of the European economies as well.
URN:NBN:fi:bof-20140807681
Keywords: E22; E23; O51; O52; 330; endogenous growth; panel data estimation; production function; R&D; technical progress; elasticity of substitution